1998
DOI: 10.1074/jbc.273.23.14315
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Inhibition of Rat Glucocorticoid Receptor Transcriptional Activation by Glycogen Synthase Kinase-3 (GSK-3)

Abstract: Transcriptional activation by the glucocorticoid receptor (GR) is regulated by both glucocorticoid binding and phosphorylation. , is a target for glycogen synthase kinase-3 (GSK-3) in vitro and in cultured mammalian cells. Increasing GSK-3 activity through its overexpression in cultured cells inhibits GR transcriptional enhancement, an effect dependent upon Thr 171 . Correspondingly, overexpression of a constitutively active form of the GSK-3 inhibitor, protein kinase B/Akt, increases GR transcriptional enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(34 citation statements)
references
References 46 publications
(42 reference statements)
2
32
0
Order By: Relevance
“…Therefore, it is possible that GSK-3 inhibitors have effects on GR activity independent of the promoter studied. However, Rogatsky et al (40) also found that the inhibition of GSK-3 by overexpression of PKB actually enhances gene activation by rat GR, consistent with the phosphorylation of GR by GSK-3 causing inhibition of GR activity. However, the overexpression of GSK-3␣ in H4IIE cells does not affect basal or dexamethasone-induced levels of G6Pase or PEPCK gene expression (Fig.…”
Section: Gsk-3 Inhibitors Have Therapeutic Potential For the Treatmenmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, it is possible that GSK-3 inhibitors have effects on GR activity independent of the promoter studied. However, Rogatsky et al (40) also found that the inhibition of GSK-3 by overexpression of PKB actually enhances gene activation by rat GR, consistent with the phosphorylation of GR by GSK-3 causing inhibition of GR activity. However, the overexpression of GSK-3␣ in H4IIE cells does not affect basal or dexamethasone-induced levels of G6Pase or PEPCK gene expression (Fig.…”
Section: Gsk-3 Inhibitors Have Therapeutic Potential For the Treatmenmentioning
confidence: 93%
“…Therefore, the molecular target(s) of GSK-3 must be required for the PEPCK and G6Pase promoters to function. The glucocorticoid receptor (GR) is reported to be a substrate for GSK-3 in vitro and in rat cells (40), with ϳ40% reduction in GR transcriptional activity caused by the overexpression of GSK-3. Therefore, it is possible that GSK-3 inhibitors have effects on GR activity independent of the promoter studied.…”
Section: Gsk-3 Inhibitors Have Therapeutic Potential For the Treatmenmentioning
confidence: 99%
“…c-Jun (41), c-Myc, C/EBP␤, ␤-catenin (see Ref. 17), glucocorticoid receptor (42), and androgen receptor (43)(44)(45)). A dual function of GSK-3 has been suggested regarding NFB where phosphorylation at two different sites results either in stabilization or in proteolytic degradation (46).…”
Section: Discussionmentioning
confidence: 99%
“…The pCMV-4 control plasmid was a gift from D. Russell. The plasmids were generated in the authors laboratories and included pCDNA3-Flag-JBD, pCGN/GSK-3wt, pCGN/GSK-3 ⌬9 , and pCGN/GSK-3 Y216F (32)(33)(34). Cells were plated at a density of 40% in triplicate wells, using six-well plates.…”
Section: Methodsmentioning
confidence: 99%